Structures of sources and their meanings in Surat Al-Muzzammil: An applied morphological-linguistic-contextual-semantic study - alzaadima, aimudalaluh muhamad alsanusii; Ahmed, Hania Farag (Tobruk University Journal of Social and Human Sciences, 2022)
The study in this research is a practical, purely analytical, grammatical, contextual study of the buildings of the sources contained in Sura al-Mazmel The research dealt with the concept of the source in language and in the terminology of grammatical and weights of the sources of the trilogy and the quadrant and the six-year, and in the applied study the research dealt with the sources contained in Sura al -Mazmel, its weights, its buildings, its lexical meanings through the analysis of sources and their actions and the monitoring of their meanings and the statement of their weights and connotations that they performed in the Qur'anic context in Sura al -Mazmel, and the usefulness of their coming with their buildings and meanings in the context of the surah each according to its place in it. The research also showed the significance of these sources in the Qur'anic interpretation books and the statement of their meanings in order to serve the Qur'anic text, and the study relied on the descriptive analytical approach. It has reached several results, the most important of which is: the multiplicity of buildings of the triangular sources in Sura al-Mazmel, which are more rose than others, which led to a change in their meanings and different connotations in the context of the Surah.